Interest and Knowledge of HIV Pre-Exposure Prophylaxis in a Unified Jail and Prison Setting. (January 2020) - Brinkley-Rubinstein, Lauren; Crowley, Christina; Montgomery, Madeline C.; Peterson, Meghan; Zaller, Nickolas; Martin, Rosemarie; Clarke, Jennifer; Dubey, Manisha; Chan, Philip A.
Pre-exposure prophylaxis (PrEP) may be an effective approach to prevent HIV among people who are currently incarcerated or who have been recently released from incarceration. However, awareness and interest in PrEP are largely unknown in this population. This study assessed 417 incarcerated men's lifetime HIV risk engagement and gauged their interest and willingness to take PrEP. Twenty percent reported ever injecting drugs and 4% ever having sex with a man without a condom; 88% had never heard of PrEP. More White men had heard of PrEP, but higher percentages of men of color were interested in learning more about PrEP and willing to take PrEP to prevent HIV. Future interventions should focus on PrEP education and uptake among individuals who are incarcerated.